Epidemiology of chronic back pain among adults and elderly from Southern Brazil: a cross-sectional study - Saes-Silva, Elizabet (Braz J Phys Ther, 2021)
BACKGROUND: Chronic back pain (CBP) can negatively affect one’s quality of life and health condition, posing significant social and economic burdens. OBJECTIVES: (1) To determine the prevalence of CBP and analyze associated factors in adult and elderly individuals in a municipality in southern Brazil; (2) to verify who sought medical attention or missed work because of back pain; and (3) to estimate the impact of CBP on selected health outcomes. METHODS: This was a population-based cross-sectional study conducted with individuals aged 18 years and older. CBP was defined as “pain for three consecutive months in the cervical, thoracic, or lumbar regions in the last year.” Demographic, socioeconomic, behavioral, and physical and mental health information was collected. The impact of CBP was assessed by the etiological fraction method. RESULTS: The prevalence of CBP was 20.7% (95% CI: 18.3, 23.0) among the 1300 study participants. The factors associated with CBP were women, elderly, smokers, obesity, and sleeping fewer hours per night, as well as those with higher mental stress levels, history of fracture, arthritis/rheumatism, and work-related musculoskeletal disorder/repetitive strain injury. One-third of those with CBP missed work (31%) and 68% visited the physician over a 12-month period. All health outcomes analyzed (poor or very poor sleep quality, regular or poor health perception, worsened quality of life, depressive symptoms, perceived sadness) were significantly associated with CBP. CONCLUSION: One in five adults or elderly reported having CBP over the previous 12 months. This condition was associated with poorer health perception, poorer quality of life, and depressive symptoms.